THE ROLE OF EDUCATIONAL TECHNOLOGIES IN INCREASING STUDENT’S SOCIAL ACTIVITIES (Ustozlar uchun, 2025)
Educational technologies play a significant role in enhancing students’ social activities by providing interactive, collaborative, and engaging learning environments. Through digital tools such as online discussion platforms, virtual classrooms, simulation software, and social media integration, students develop communication skills, teamwork, and social responsibility. The use of educational technologies fosters a sense of community, encourages active participation, and supports peer-to-peer learning. This study explores the ways in which educational technologies influence students’ social behavior, engagement in group activities, and their ability to collaborate effectively. The findings suggest that integrating technology into the learning process positively impacts students’ social skills, motivation, and overall participation in academic and extracurricular activities.